Literatura como experiência - Costa, André Luiz Ribeiro (2018)
This work is divided into two parts: a short novel and a theoretical essay that tries to understand the process of creating the novel and propose a reflection on its theme. The novel was written in long scenes connected by short summaries and shows a week in the protagonist's existence, a week in which the life he was accustomed declines and changes. During the narrative, three works of art are shown: a movie, internet videos and a performance. These works of art acts as catalysts for the novels theme, works that are based in referents directly from reality and that alters the perception of the protagonist on his own experience. The theoretical essay, based mainly on the thought of Deleuze and Guattari, tries to understand how literature can depart from reality to create something that is not real and yet exerts an influence on reality. Considering the idea of percepts and affects, we have assemblages that are formed through the work of art, and both the novel and the essay, in different ways, pretend to show this. The essay also describes a course of creation of the novel, showing the beginning of writing and how the narrative has changed during the process.